Induction of acid resistance in Bifidobacterium: a mechanism for improving desirable traits of potentially probiotic strains - Collado, M.C; Sanz, Y (Journal of Applied Microbiology, 2007)
To generate stable acid-resistant Bifidobacterium strains isolated from human subjects and characterize the phenotypic changes of the acid-resistant derivatives. The ability of 20 Bifidobacterium strains isolated from human faeces to survive to simulated gastrointestinal transit was evaluated, showing major reductions in viability (0·25-5·8 logarithmic units) because of gastric stress conditions. Six acid-sensitive strains belonging to the species Bifidobacterium longum and Bifidobacterium catenulatum were submitted to prolonged incubation at pH 2·0 to generate acid-resistant strains. The acid-sensitive and acid-resistant derivative strains were characterized to determine the changes associated with the acquisition of an acid-tolerant phenotype. The acid-resistant derivatives showed better ability to grow in the presence of bile salt (1-3%) and NaCl (6-10%) and higher resistance at elevated temperatures (60-70°C, 10 min) than the parental strains. The acid-resistant derivatives displayed higher fermentative ability, and enzymatic activities. These strains also showed higher sensitivity to most of the tested antibiotics than the parental strains. The stress tolerance of B. longum and B. catenulatum strains was improved by prolonged exposure to acid stress conditions. Some of the generated strains also seemed to have enhanced metabolic properties of relevance for probiotic applications. The successful use of prolonged exposures to acid stress to improve the stability of human bifidobacteria indicates that this strategy could be useful for the production of robust probiotic strains, but involves other phenotypic changes that required an individual characterization.